2020
DOI: 10.1155/2020/1018793
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vertical Facial Growth Pattern on Herbst Appliance Effects in Prepubertal Patients: A Retrospective Controlled Study

Abstract: Introduction. The Herbst device is widely used for correction of class II malocclusions; however, most of the researches carried out on the Herbst appliance in literature do not take into account patients with a different mandibular divergence. The aim of this study was to investigate the effects of Herbst on dental and skeletal structures and to evaluate possible influence of vertical facial growth patterns. Methods. A retrospective study was conducted on lateral cephalograms of 75 growing patients (mean age:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The complexity of the malformation itself requires a multidisciplinary approach to minimize complications and discomforts for the paediatric patients and the paediatric dentist must be part of the cleft-multidisciplinary team. Moreover, the often-severe malocclusions these patients present requires complex and early orthodontic treatment, for which tooth health is necessary, as they represent the support for any orthodontic appliance [6][7][8][9][10]. In addition, the higher prevalence of tooth anomalies in shape, number, and enamel composition in CLPA patients determine a higher risk for severe carious lesions, also in primary dentition [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of the malformation itself requires a multidisciplinary approach to minimize complications and discomforts for the paediatric patients and the paediatric dentist must be part of the cleft-multidisciplinary team. Moreover, the often-severe malocclusions these patients present requires complex and early orthodontic treatment, for which tooth health is necessary, as they represent the support for any orthodontic appliance [6][7][8][9][10]. In addition, the higher prevalence of tooth anomalies in shape, number, and enamel composition in CLPA patients determine a higher risk for severe carious lesions, also in primary dentition [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the dentist is involved in the treatment of cleft patients, as the prevalence of dental anomalies and subsequent malocclusion is much higher than in the general population [4,5]. Therefore, orthodontic and restorative treatments are often necessary [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that the third molar had the greatest variation in morphology, size, and time of development and eruption compared with the other teeth. Thus, the assessment of its developmental stages and relation to chronological age might not be reliable [ 32 , 37 , 38 ]. However, the results of our study were in agreement with other findings demonstrating that assessment of the third molar developmental stages was a reliable and useful method for major age estimation [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, orthodontic therapy involving specific biomechanics and anchorage systems is required to generate complex dental movement and to eliminate dentoalveolar compensations that have occurred over time. Generally, comprehensive prosthetic rehabilitations can be listed into four categories, according to specific clinical characteristics, i.e., (1) multiple missing teeth, (2) worn anterior dentition, (3) excessive vertical overbite, and (4) tilted molars [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Conversely, conformative rehabilitation is characterized by minor corrections of teeth position without significant change of static or dynamic occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…The mock-up clinical test represents a critical stage in the rehabilitation process since the mock-up enhances the communication with the patient showing a realistic preview of the final aesthetic rehabilitation and providing clinicians with a better understanding of the patient’s aesthetic expectations [ 9 , 10 ]. As a consequence, the patient’s satisfaction with the treatment strictly depends on the consistency of the final product with the mock-up [ 11 , 12 ]. Finally, this stage is important to clinically test and validate the functional adaptability of the prosthetic project.…”
Section: Introductionmentioning
confidence: 99%